Continuum between conservation and use of plant genetic resources: strengthening pre breeding at ICARDA - Amri, Ahmed (International Center for Agricultural Research in the Dry Areas, 2023)
The continuum between conservation and use of plant genetic resources: strengthening pre-breeding at ICARDA.